Business as Usual in Unusual Times - Vibeke Krane; Liv Hanson Ausland; Ellen Andvig; Trude Klevan (Journal of Comparative Social Work, 2021)
Background: The COVID-19 pandemic has severely affected the daily lives and well-being of children and families. During the lockdown of Norway in spring 2020, many families were socially isolated and left with little support from their networks. Children and young people had limited contact with teachers, peers and other positive social contacts. The lockdown also affected the daily running of the Norwegian child welfare services (CWS), which are obliged to provide help and support to children at risk and their families.